PENGARUH IMPLEMENTASI KEBIJAKAN ZONASI PENDIDIKAN TERHADAP MOTIVASI BELAJAR SISWA SD NEGERI 2 SOPAI TORAJA UTARA - SILAS, REINALDO EFRAIM; LENGKONG, FLORENCE; LALOMA, ALDEN (Sam Ratulangi University, 2021)
This study aims to determine the effect of the implementation of the zoning policy onstudents' learning motivation at SD Negeri 2 Sopai.This research was conducted at SD Negeri 2 Sopai Toraja Utara. The data collection techniques used inthis study were questionnaires, interviews, and observation documentation.The data analysis method used is a simple linear regression test method, validity test, reliability test andproduct moment correlation test to determine the education zoning policy variable has a positive andsignificant effect on the learning motivation of SD Negeri Sopai students.Based on the results of the research that has been done, there is a positive influence on the learningmotivation of SD Negeri 2 Sopai students and the implementation of the education zoning policy has astrong and significant correlation to the development of student motivation in SD Negeri 2 Sopai.Keywords: Policy Implementation, School Zoning, Learning Motivation